2017
DOI: 10.1016/j.jmacro.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Global banking and the conduct of macroprudential policy in a monetary union

Abstract: This paper questions the role of cross-border lending in the definition of national macroprudential policies in the European Monetary Union. We build and estimate a two-country DSGE model with corporate and interbank cross-border loans, Core-Periphery diverging financial cycles and a national implementation of coordinated macroprudential measures based on Countercyclical Capital Buffers. We get three main results. First, targeting a national credit-to-GDP ratio should be favored to federal averages as this rul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Most of the literature has examined macroprudential policy coordination in the European Monetary Union (EMU), but there is no consensus on the size of coordination gains. For example, Poutineau and Vermandel (2017) built a two‐country DSGE model that included cross‐border loans and the deviation of core‐peripheral financial cycle, and found that there are still doubts about raising macroprudential policy formulation to the supranational level, and supported the establishment of macroprudential policies at the national level. However, the DSGE model of the monetary union between the two countries was constructed by Agénor, Jackson, Kharroubi, et al (2021) to compare the different welfare of non‐cooperative Nash equilibrium and cooperative equilibrium in macroprudential policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the literature has examined macroprudential policy coordination in the European Monetary Union (EMU), but there is no consensus on the size of coordination gains. For example, Poutineau and Vermandel (2017) built a two‐country DSGE model that included cross‐border loans and the deviation of core‐peripheral financial cycle, and found that there are still doubts about raising macroprudential policy formulation to the supranational level, and supported the establishment of macroprudential policies at the national level. However, the DSGE model of the monetary union between the two countries was constructed by Agénor, Jackson, Kharroubi, et al (2021) to compare the different welfare of non‐cooperative Nash equilibrium and cooperative equilibrium in macroprudential policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first approach raises the question of the relevance of a common policy to correct specific financial imbalances (Dehmej and Gambacorta, 2018). Indeed, given the existence of structural heterogeneities, the conduct of a single macroprudential policy would be likely to accentuate divergences and financial imbalances within a monetary zone (Poutineau and Vermandel, 2018).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The macroprudential instrument in the form of the loan-to-value ratio (LTV) associated with the single monetary policy allows for the reduction of financial imbalances within the national economy. Poutineau and Vermandel (2018), using a neo-Keynesian model, analyze the relevance of the implementation of macroprudential policy within a heterogeneous monetary union. Due to the structural heterogeneities that feed the heterogeneity of financial cycles within the euro area, the conduct of national macroprudential policy is effective in preserving financial stability in contrast to joint action.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…That is a reason not to coordinate within the euro area. However, in the case of a common situation within the euro area, research shows that there would be benefits from coordinated actions (Rubio and Carraso-Gallego (2016)) while other conclude there is no need for it (Poutineau and Vermandel (2017)).…”
Section: The Long List Of Questions Waiting For Answersmentioning
confidence: 99%